Dilemmas of public and state administration - Mulec, Breda (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2023)
The role of education systems is crucial in creating bilingualism and multilingualism. Based on domestic and foreign literature and structured interviews with public officials in North Macedonia and Italy, the article analyses the solutions and incentives for institutional bilingualism, which have proven insufficient thus far. It also offers a model of multilingualism as a concept of an ideal environment where speakers can communicate using multiple languages. The impact of new information and communication technologies on language learning and use in bilingual areas and their contribution to the creation of an ideal environment conducive to multilingualism will also be examined. The data obtained shows, among other things, that artificial intelligence is also revolutionising language use and learning. Nonetheless, despite rapid progress, human communication in different languages cannot be replaced by artificial algorithms.
Keywords: bilingualism bonus; bonus za dvojezičnost; državna uprava; immigrants; institucionalna dvojezičnost; institutional bilingualism; javna uprava; javni sektor; javni uslužbenci; manjšine; minorities; priseljenci; public administration; public employees; public sector; state administration